2017
DOI: 10.1096/fj.201600939rr
|View full text |Cite
|
Sign up to set email alerts
|

Role of telomeric repeat–containing RNA in telomeric chromatin remodeling during the early expansion of human embryonic stem cells

Abstract: This study aimed to explore the role of telomeric repeat-containing RNA (TERRA) in telomeric chromatin remodeling during the early expansion of human embryonic stem cells (hESCs). During the derivation of hESCs, histone demethylation in the telomeric region facilitates telomerase-mediated telomere elongation. An adequate telomere repeat is essential for hESCs to acquire and/or maintain the unlimited symmetric division, which suggests that there is a link between pluripotency and telomere maintenance. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(85 reference statements)
2
4
0
Order By: Relevance
“…Finally, we also confirmed increased TERRA expression as the result of TRF1 abrogation in keratinocytes from Terf1 Δ/Δ K5-Cre newborn mice, which lack TRF1 expression (Figure 5D). These results are in agreement with previous findings from other groups in human cells (Porro et al, 2014; Zeng et al, 2017; Sadhukhan et al, 2018), which also show TERRA increase upon TRF1 depletion. Other studies, however, showed that depletion of TRF1 in mouse immortalized MEFs did not increase TERRA levels (Sfeir et al, 2009), and that downregulation of TRF1 by siRNA in the immortalized mouse myoblast cell line C2C12 reduced the expression of TERRA (Schoeftner and Blasco, 2008).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Finally, we also confirmed increased TERRA expression as the result of TRF1 abrogation in keratinocytes from Terf1 Δ/Δ K5-Cre newborn mice, which lack TRF1 expression (Figure 5D). These results are in agreement with previous findings from other groups in human cells (Porro et al, 2014; Zeng et al, 2017; Sadhukhan et al, 2018), which also show TERRA increase upon TRF1 depletion. Other studies, however, showed that depletion of TRF1 in mouse immortalized MEFs did not increase TERRA levels (Sfeir et al, 2009), and that downregulation of TRF1 by siRNA in the immortalized mouse myoblast cell line C2C12 reduced the expression of TERRA (Schoeftner and Blasco, 2008).…”
Section: Resultssupporting
confidence: 94%
“…Here, we demonstrate that TERRA can also bind to PRC2 sites in the genome that are dependent on TRF1. More importantly, we show that TRF1 depletion causes a dramatic increase in TERRA expression, in agreement with previous observations in human cells that show increased levels of TERRA upon TRF1 downregulation (Porro et al, 2014; Zeng et al, 2017; Sadhukhan et al, 2018). This upregulation of TERRA expression coincides with an increased binding of TERRA to genomic regions where PRC2 is also increased upon TRF1 depletion and that are important in controlling pluripotency and differentiation.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in somatic and ES cells, short telomeres or altered telomeric DNA structure can promote TERRA transcription (Schoeftner and Blasco 2008 ). Interestingly, in human somatic cells, H3K9me3 enrichment at telomeres might repress TERRA transcription, presumably through the action of SUV39H1 (Arnoult et al 2012 ), while in human ES cells, reduction of TERRA expression impairs SUV39H1 recruitment and promotes telomere lengthening (Zeng et al 2017 ). Thus, certain TERRA-dependent targeting of chromatin regulator might be cell specific.…”
Section: Introductionmentioning
confidence: 99%
“…TRF1 is overexpressed in ES and iPS cells (induced pluripotent cells), in de-differentiated cells, as well as in the blastocyst inner membrane [ 96 , 97 ]. On the other hand, TRF1 depletion led to an important increase in TERRA levels [ 87 , 98 ]. Moreover, TRF1 has been previously shown to bind to the H3K27me3-rich regions in the genome and to interact with PRC2 in human models [ 79 ].…”
Section: Transcripts With Telomere-related Functionsmentioning
confidence: 99%